Incidence of Psoriatic Arthritis in Patients with Skin Psoriasis and Associated Risk Factors: A Retrospective Population-based Cohort Study in Swedish Routine Clinical Care - Ingrid Lindberg; Mathias Lilja; Kirk Geale; Haijun Tian; Craig Richardson; Amie Scott; Amra Osmancevic (Medical Journals Sweden, 2020)
The incidence of psoriatic arthritis in patients with psoriasis is unclear; existing estimates differ by a factor of ten. Complete population-level data is needed to provide accurate estimates with high confidence. A total of 123,814 adults with psoriasis, free from pre-existing psoriatic arthritis, were identified in population-based data from secondary care in Sweden during 2007 to 2017. Incidence was calculated as the number of psoriatic arthritis diagnosis events per 100 patient-years. Time to diagnosis was assessed using cumulative incidence and Cox proportional hazards models to identify risk factors. Incidence of psoriatic arthritis in patients with psoriasis was 1.69 per 100 patient-years (95% confidence interval 1.65-1.72) overall, and 1.48, 3.00, and 5.49 per 100 patient-years in patients with mild, moderate and severe psoriasis, respectively. Risk of psoriatic arthritis was 3.2 times higher amongst patients with severe psoriasis compared with mild disease. Dermatologists should regularly assess risk factors for psoriatic arthritis in clinical practice in order to improve the detection of psoriatic arthritis.